Evaluating the Efficacy of Giant Lira(Melia Azedarach) extract in the controlling the Pod Borer pest in Cowpea(Vigna Unguiculata) - Morris Lonya (Uganda Christian University, 2025)
There are limited eco-friendly approaches which are IPM based to control the pod borer in cow pea. This Research aimed at assessing the effectiveness of Giant lira (Melia azedarach) extract as a natural pod borer control agent on infested Cowpea crops (Vigna Unguiculata).The experiment of pod borer was conducted at the faculty of Agricultural Sciences department in the field for the bioactivity in Uganda Christian University demonstration field using Random Complete Design (RCBD) with three replicates and an area of 5x4m2 was used for the experiment. Data was collected on the Number of live larva, dead larva and Pest Severity. The results indicated there was a significant difference P-Value (0.002) amongst different giant lira extracts on the number of live larva of the pod borer damage on cowpea. The control recorded the highest number of live larva 1.90±0.62b and T4 recorded the lowest number of live larva 1.57±0.77a.There was a significant difference (P<.001) in the effect of giant lira on the damage caused by the pod borer on the flowers among the different concentrations of the giant lira. However, T1 (0%) which was the control, the damage levels were higher with 3.44±0.85 while at T4 (80%) concentration had the lowest flower damage of1.944±0.80.Therefore, the concentration T4 (80%) of giant lira is best for controlling pod borers and increased yields. This has a useful component of an integrated pest management (IPM) strategy since the compounds are known for their low toxicity on cow pea plants.
Thesis